Efeitos da injunção da base nas orientações interior e exterior e nas coordenadas do espaço objeto em imagens obtidas com a estéreo vídeo-câmara de um sistema móvel de mapeamento - Souza Espinhosa, Dalila Rosa [UNESP]; Custodio da Silva, Joao Fernando [UNESP]; Galo, Mauricio [UNESP] (Universidade Federal do Paraná (UFPR), Centro Politecnico, 2008)
In general, a land-based mobile mapping system is featured by a vehicle with a pair of video cameras mounted on the top and positioning and navigation sensors loaded in the vehicle. Considering the pair of video cameras mounted on the roof of the vehicle as a stereo camera pointing forward with both optical axes parallel to each other and orthogonal to the stereo base, whose length is 0.94 m, this paper aims at analyzing the interior and exterior camera orientation and the object point coordinates estimated by phototriangulation when the length constraint related to the stereo base is considered or not. The results show that the stereo base constraint has effect ouver the convergence estimation, but does it neither improves the object point coordinate estimation at significance level of 5% and nor it influences the interior orientation parameters. Finally, it has been noticed that the optical axes are not truly parallel to each other and orthogonal to the stereo base. Additionally, it has been observed that there is a convergence of approximately 0.5 degrees in the optical axes and they are not in the same plane (approximately 0.8 degrees deviation).
Effects of the base constraint on the interior and exterior orientation and on the object point coordinates in images obtained from the stereo video camera of a mobile mapping system
Keywords: mobile mapping; stereo base constraint; stereo video camera